Effect of high temperature aging on microstructure and mechanical properties of HR3C heat resistant steel. (February 2014) - Bai, X.; Pan, J.; Chen, G.; Liu, J.; Wang, J.; Zhang, T.; Tang, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Microstructure and mechanical properties of the HR3C austenite heat resistant steel were investigated after artificial aging at 650°C for time up to 3000 h. The results show that as the aging time increased, the room temperature tensile and impact fracture mechanisms of the HR3C steel change from trans- to intergranular fracture. M23C6 type carbides and MX type carbonitrides continuously precipitate during aging, leading to the change of the mechanical properties and fracture mode of the steel. Moreover, the dissolution of the coherent twins and the transformation from the incoherent twins to the thermodynamically stable austenite subgrains have great effects on the mechanical properties of the aged steel, too. When increasing the aging time to ≧2000 h, the microstructure and mechanical properties of the steel are nearly constant, indicating a good thermal stability of the HR3C steel at elevated temperature.